Produção de forragem hidropônica em solução orgânica - Morselli, Larri Antônio (2010)
Hydroponic forage production using vermicompost obtained from manure of animals is a way to solve problems related to the production costs, lack of water in Summer and cold Winter. The adoption of this practice can be an alternative in the production of milk, allowing the inclusion of small farmer into an increasing consumer market of organic products. In this sense two experiments were conducted in high tunnel greenhouse type at the Campo Didático e Experimental of Departamento de Fitotecnia/Faculdade de Agronomia Eliseu Maciel/Universidade Federal de Pelotas/RS/UFPEL , in order to evaluate the yield and nutritional quality of fodder plants produced in hydroponically with organic solution. Randomized blocks experimental design was used for both experiments, with eight treatments (two crops two recommend base solutions and two earth-worm compost) and five replications totalizing 40 plots. The following variables where evaluated: plant height, fresh and dry mass at 14 days after sowing and the qualitative variables: crude protein, crude fiber, fiber in acid detergent and neutral detergent, ether extract and ashes. The evaluated crops were: wheat (Triticum aestivum L.) and black oats (Avena strigosa Schreb) in the first experiment and maize (Zea mayz L.) and millet (Pennisetum glaucum L.) in the second experiment. Eisenia foetida earth-worm composts in liquid form, obtained from bovine and pig manure, according two nitrogen recommendations 190.6 and 105.9 mg L-1 of N respectively, by Santos et al. (2003) and Neves (2001) - were used as fertilizer sources to formulate organic nutrient solutions. There was no significant difference between wheat and black oats in relation to plant height, fresh mass, crude protein and ashes. Concerning to dry mass and ether extract oats presented higher values, while wheat presented higher crude fiber, fiber in neutral detergent and fiber in acid detergent than oats. Bovine and pig manure earth-worm composts as well as Santos and Neves base solutions did not show significant differences for both crops. At the second experiment maize and millet crops presented no differences for crude fiber, neutral detergent fiber and acid detergent fiber. Maize presented much higher plant height, fresh and dry mass values, while millet presented higher crude protein, ether extract and ashes. The obtained results point out that it is possible to use both earth-worm composts as well as the two base solutions without loss in yield quality and bromatological composition for wheat, oats and maize cultivation. Among the fodder crops, the decision will follow the farmer choice or animals demand at the moment.